Absence of wide-zone, alpha-hemolytic streptococci in children with pharyngitis. - Saitz, E W (1976)
Wide-zone, alpha-hemolytic streptococci are potential sources of false-positive throat cultures since they can be misinterpreted as beta-hemolytic streptococci. However, quantitative information regarding their occurrence in sick children was not available. Throat swabs from 312 children with pharyngitis were processed conventionally and also with pour-plate methods and examination of the positive cultures under magnification. One-third of all cultures were positive for beta-hemolytic streptococci. There were no significant differences in the number of positive cultures among or between the different methods. Wide-zone, alpha-streptococci were found in none of the cultures. Therefore, they are unlikely to be a common cause of false-positive cultures in children with pharyngitis.